2018
DOI: 10.1149/2.0331814jes
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide/α-MnO2 Binary Nanosheets Based Non-Enzymatic Biosensor for Pico-Molar Level Electrochemical Detection of Biomarker (Guanine) in DNA Sample

Abstract: We reported Graphene Oxide/α-MnO 2 binary nanosheets (GO/α-MnO 2 BNSs) Based Non-Enzymatic Biosensor for the detection of guanine using selective and ultra-sensitive electrochemical method. In this work, GO/α-MnO 2 BNSs synthesized using simple and cost-effective ultra-sonication method. As produced GO/α-MnO 2 BNSs were investigated by FE-SEM, TEM, EDX, FT-IR, XRD, EIS and electrochemical methods. The electrochemical oxidation behavior of guanine at the GO/α-MnO 2 BNSs modified electrode was evaluated by cycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The exploitation of nanomaterials in electrochemical bio-sensors have been intensively explored owing to enhanced surface to volume ratio, thereby opening prospects of diverse functionalization, and quantum confinement effects [15][16][17][18][19][20]. Among the vast array of nanomaterials, MnO 2 nanostructures have garnered considerable interest due to its non-toxic nature which makes them potential biocompatible sensing platforms [21][22][23]. Bai et al reported the voltammetric detection of choline using choline oxidase (ChOx)/MnO 2 /chitosan modified glassy carbon electrode [24].…”
Section: Introductionmentioning
confidence: 99%
“…The exploitation of nanomaterials in electrochemical bio-sensors have been intensively explored owing to enhanced surface to volume ratio, thereby opening prospects of diverse functionalization, and quantum confinement effects [15][16][17][18][19][20]. Among the vast array of nanomaterials, MnO 2 nanostructures have garnered considerable interest due to its non-toxic nature which makes them potential biocompatible sensing platforms [21][22][23]. Bai et al reported the voltammetric detection of choline using choline oxidase (ChOx)/MnO 2 /chitosan modified glassy carbon electrode [24].…”
Section: Introductionmentioning
confidence: 99%
“…2D layered materials have fascinated particular consideration owing to their outstanding physicochemical features and potential for creating progressive electronic devices. [14][15][16] Molybdenum disulfide (MoS 2 ) is considered to be a layered transition metal dichalcogenide, consisting the layered structural form of S-Mo-S, where the Mo atoms are sandwiched between two layers of closely packed S atoms. The strong covalent bond interaction of Mo-S and the interactions between adjustment S layers through van der Waals forces.…”
mentioning
confidence: 99%
“…Recent advancements in nanotechnologies have enhanced the attachment operations. [18][19][20] Although many biosensing schemes based on nanostructured materials have been developed, [21][22][23][24] the real applications of the existing piece-by-piece nanofabrication technologies are limited due to time consumption and relative low reproducibility. Electrochemical impedance spectroscopy (EIS) 25,26 has been widely used in many electrochemical applications [27][28][29][30] because of its high sensitivity, low detection cost, requirement of few test samples, simple operation procedures, and ability to be used for gas and liquid phase environmental detection.…”
mentioning
confidence: 99%